2 Development of a sers-nanoparticle based system for the multiplex detection of vascular adhesion molecules. (1st April 1997) - Noonan, Jonathan; Asiala, Steven; Grassia, Gianluca; MacRitchie, Neil; Gracie, Kirsten; Faulds, Karen; McInnes, Iain B; Garside, Paul; Graham, Duncan; Maffia, Pasquale
Abstract : Surface-enhanced Raman spectroscopy (SERS) is an emerging molecular imaging technique suitable for the highly sensitive simultaneous detection of multiple analytes. We aimed to apply SERS for the multiplex detection of adhesion molecules in human umbilical vein endothelial cells and macrophages in vitro, as a step towards applying this technology for simultaneously detecting multiple biomarkers of vascular inflammation and atherosclerotic plaque instability in vivo . Immunofluorescent microscopy and flow cytometry identified the expression of intercellular adhesion molecule (ICAM)−1, vascular cell adhesion molecule (VCAM)−1 and p-Selectin on human umbilical vein endothelial cells (HUVECs) following stimulation with 10 ng/ml TNFα for 24 hours. Phorbol 12-myristate 13-acetate (PMA) differentiated THP-1 macrophage-like cells expressed only ICAM-1 in both unstimulated and 24 hours 10 ng/ml TNFα stimulated conditions. Gold nanoparticles were PEGylated and functionalized with Raman reporters, in order to endow a specific pre-determined SERS signal, alongside antibodies against the desired adhesion molecule targets. This provided 'nanotags' configured as follows (antibody/Raman reporter); anti-ICAM-1/BPE; anti-VCAM-1/PYOT, anti-p-Selectin/PPY, IgG Isotype Control/DP. TNFα stimulated HUVEC were exposed to a mixture of all nanotags simultaneously (final concentration of 20 ug/L) and were subsequently imaged using SERS microscopy. This rational allowed for the simultaneous detection and discrimination of ICAM-1, VCAM-1 and p-Selectin on activated HUVEC. Adhesion molecules were detectible as soon as 15 min following nanotag addition, while IgG control nanotags produced negligible signal at all concentrations and time points investigated. Following simultaneous exposure to all nanotags, SERS imaging identified the expression of ICAM-1 on PMA differentiated TNFα stimulated THP-1, with little-to-no contribution from anti-VCAM-1, anti-p-Selectin, or IgG control nanotags. Here we have developed a SERS-based molecular imaging methodology for the multiplex detection of adhesion molecules in vitro .